2013
DOI: 10.1590/s1516-89132013000500016
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of mixed cultures of yeast and lactic acid bacteria in cider conditions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…O. oeni is one of the main LAB contributing to MLF in cider. It has always been detected along with other LAB species (Salih et al 1988 ; Sánchez et al 2010 , 2012 ; Dierings et al 2013 ). This contrasts with its predominance in wine, probably because cider has lower alcohol content (1.2–8%) and sometimes a higher pH than wine, which makes it more suitable for the growth of non- O. oeni species.…”
Section: Apple Cider: the Second Homementioning
confidence: 98%
“…O. oeni is one of the main LAB contributing to MLF in cider. It has always been detected along with other LAB species (Salih et al 1988 ; Sánchez et al 2010 , 2012 ; Dierings et al 2013 ). This contrasts with its predominance in wine, probably because cider has lower alcohol content (1.2–8%) and sometimes a higher pH than wine, which makes it more suitable for the growth of non- O. oeni species.…”
Section: Apple Cider: the Second Homementioning
confidence: 98%
“…Dierings et al . () found a similar variation between the population of OXYs in apple musts (10 3 –10 6 CFU/mL). The LAB count was similar in the musts of the Gala cultivar, but showed large variations in the commercial and industrial musts of the Fuji cultivar, with values of 10 3 –10 5 CFU/mL, respectively.…”
Section: Resultsmentioning
confidence: 55%
“…In fresh apple musts, the yeasts population varies between 10 3 and 10 4 CFU/mL (Le Quéré and Drilleau ; Dierings et al . ). The populations of OXY were very similar between the industrial and commercial apples, but showed large variations among cultivars (10 4 –10 7 CFU/mL).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Differences in observed relationships between fermentation temperature and the share of esters in the aromatic profiles of the analyzed ciders were due to differences between fermentation settings (contents of microelements, acidity or contents of extract). Ciders and cider musts are characterized by a much lower dry matter concentration, density, acidity and nitrogen content than wine musts [ 48 ]. Other important groups of compounds responsible for the cider aroma are alcohols and carboxylic acids.…”
Section: Discussionmentioning
confidence: 99%